Anti-GM1 antibodies in patients with Guillain-Barre syndrome. - Leonard H. van den Berg; J. Marrink; Agnes Jager; Herman de Jong; Gustaaf W. van Imhoff; Norman Latov; Saud Sadiq (1992)
Anti-GM1 antibodies were measured in 22 patients with the Guillain-Barré syndrome (GBS) and compared with anti-GM1 antibody activity in patients with other neurological or immunological diseases and in normal subjects. Four out of 22 patients with GBS had raised IgM, IgG, or IgA anti-GM1 antibody activities. All four patients were tetraparetic with only minimal or no sensory deficit. Three of the patients had highly raised antibody activity and showed severe residual deficits, while of the remaining patients with GBS, only one remained severely affected. One patient had anti-GM1 antibodies specific for GM1, whereas the other three patients showed antibody activity with asialo-GM1 or GD1b. The presence of anti-GM1 antibodies may define a subgroup of patients with GBS who have a poor prognosis.